Nutritional and qualitative comparison of temperate fruits from conventional and organic orchards - Marziyeh Rabiee; Behzad Kaviani; Shahram Sedaghathoor; Alireza Eslami (Scientific Reports, 2025)
Abstract This research was conducted to compare the quality and nutritional profile of temperate fruits cultivated in conventional and organic orchards. Sampling was done in Iran from four orchards (two organic and two conventional). Ten fruits were sampled in three replicates in each of the organic and conventional orchards. Some traits such as the content of carotenoid, chlorophyll, ascorbic acid, phenolics, protein, soluble solids (TSS) and calcium (Ca), copper (Cu), zinc (Zn), iron (Fe), potassium (K), sulfur (S) and phosphorus elements were measured in the fruits and leaves. This study aims to evaluate the variability in chemical and nutritional quality parameters among various temperate fruit species sourced from both organic and conventional production methods. The research findings indicate that fruits cultivated in organic orchards exhibit superior quality and enhanced nutritional profiles compared to those grown conventionally. Specifically, the highest levels of carotenoids, chlorophyll, protein, and essential minerals were observed in the organic orchard. Notably, the interaction between orchard type and fruit variety revealed that organic mulberry displayed the highest concentrations of chlorophyll, protein, copper, and potassium. In contrast, organic grapes and figs presented elevated total soluble solids, copper, zinc, and iron levels. These results underscore the benefits of organic farming practices in producing nutritionally rich fruits.